2003
DOI: 10.1023/b:jopc.0000005459.00492.60
|View full text |Cite
|
Sign up to set email alerts
|

A Capillary Electrophoresis Technique for Evaluating Botulinum Neurotoxin B Light Chain Activity

Abstract: Botulinum neurotoxin B (BoNT/B) produces muscle paralysis by cleaving synaptobrevin/vesicle-associated membrane protein (VAMP), an 18-kDa membrane-associated protein located on the surface of small synaptic vesicles. A capillary electrophoresis (CE) assay was developed to evaluate inhibitors of the proteolytic activity of BoNT/B with the objective of identifying suitable candidates for treatment of botulism. The assay was based on monitoring the cleavage of a peptide that corresponds to residues 44-94 of human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…With UV detection the absorbance of product, P2, was routinely masked by the background absorbance of the HNTE running buffer although peaks for substrate, S, and product, P1, were visible (data not shown). Similar masking effects were reported for UV detection in CE separations of reaction products of BoNT/B LC in HEPES buffer [21]. Hence in order to facilitate detection and quantitation of products, detection methods based on laser-induced fluorescence were developed.…”
Section: Comparison Of Ce and Hplc For Separation Of Bont/a Reaction mentioning
confidence: 67%
See 1 more Smart Citation
“…With UV detection the absorbance of product, P2, was routinely masked by the background absorbance of the HNTE running buffer although peaks for substrate, S, and product, P1, were visible (data not shown). Similar masking effects were reported for UV detection in CE separations of reaction products of BoNT/B LC in HEPES buffer [21]. Hence in order to facilitate detection and quantitation of products, detection methods based on laser-induced fluorescence were developed.…”
Section: Comparison Of Ce and Hplc For Separation Of Bont/a Reaction mentioning
confidence: 67%
“…The same labeling reagent has been used in CE-LIF for characterization of VAMP-thioredoxin fusion protein, developed as a potential substrate for BoNT/B [20]. A detailed CE-based study of BoNT/B light chain (LC) activity using UV detection has been reported, although no results were given for quantitation in the presence of potential modulator compounds [21].…”
Section: Introductionmentioning
confidence: 99%
“…CZE was used to study b-amyloid and its aggregation [275], botulinum neurotoxin B light chain activity [276], nonenzymatic posttranslation modifications on BSA [277], aminoacyl-tRNA synthetase localized in cell nucleus [278], protein-protein interactions [279], aggregation and denaturation of antibodies [280], glycosylation of murine erythropoietin [281], PEGylation of proteins [282], glutamine deamidation in proteins [283], complexation of apomyoglobin with Coumarin 153 [284], reaction of FQ with ovalbumin [285], interaction of GFP with calcium [286], noncovalent complexation in myoglobin [287], DNA-protein interactions [288][289][290], binding fucoidan to antithrombin [291], retinoic acid to b-lactoglobulin B [292], and binding phospholipid and glycosaminoglycan to human b 2 -glycoprotein [293].…”
Section: Other Proteinsmentioning
confidence: 99%
“…Capillary electrophoresis (CE) has been emerging as another promising way for analysing BoNT's activity because of the extremely small sample volume needed per analysis and high throughput potential [19,22]. During the assay, CE is used to separate the product from the peptide substrate after reaction with BoNTs.…”
Section: Introductionmentioning
confidence: 99%
“…During the assay, CE is used to separate the product from the peptide substrate after reaction with BoNTs. Since the toxin activity is assayed in solution phase, the CE format allows kinetic analyses of toxin activity [22]. However, due to the small light-path length in CE, it is necessary to use sensitive detectors to detect the low concentrations of BoNT.…”
Section: Introductionmentioning
confidence: 99%